Effects of energy saving and emission reduction in the heating system part of the energy-saving renovation of existing buildings—Based on China's first residential area with a 75% energy saving standard. Issue 1 (January 2021) - Zhang, Meijie; Liu, Yiyang; Shen, Zebin
Abstract: The energy-saving renovation of existing buildings in China has achieved initial results and improved the living conditions of residents. This article analyzes the data on the renovation of the heating system of China's first residential area with an energy-saving standard of 75%. Through data measurement, recording and calculation, the effect of energy saving and emission reduction after heating system transformation is obtained. At the same time, using the graph to obtain the curve of the heating flow with the outdoor temperature, it is concluded that the climate compensator has a significant role in intelligent regulation and still has a 5% energy saving potential.